Woodball Training Pattern Book at Silampari Woodball Academy - Isnani, Risma; Supriyadi, Muhammad; Syafutra, Wawan (STKIP Paasundan Press, 2024)
The purpose of this study focuses on the development of print media for woodball practice patterns at Silampari woodball academy. The approach used by ADDIE has 5 stages, namely: (1) Analysis (2) Design (3) Development (4) Implementation (5) Evaluation. The data collection applied in the study was direct observation, question and answer with samples and questionnaires. The data processing technique utilizes the validity analysis method of 3 experts, the validity analysis of media experts is 0.81%, the validity analysis of linguists is 0.87%, the validity analysis of the material is 0.87%, from the results obtained from 3 experts, it can be concluded that the media developed is very valid, then based on the analysis of the practicality questionnaire by testing athletes with one to one tests, small groups and coaches get a score of 86% so that the media made is very practical, Then analyze the effectiveness by conducting a pre-test and post test as well as observation of Silampari woodball academy athletes for pre-test of 20 athletes, only 8 athletes who meet the criteria and for post test 15 athletes who meet the criteria of 20 people based on observation sheets.